Systematic literature review of traits and outcomes reported in randomised controlled trials of asthma with regular dosing of inhaled corticosteroids with short-acting β 2 -agonist reliever, as-needed ICS/formoterol, or ICS/formoterol maintenance and reliever therapy - Roche, Nicolas; Yorgancıoğlu, Arzu; Cruz, Alvaro A; Garcia, Gabriel; Lavoie, Kim L; Abhijith, P G; Verma, Manish; Majumdar, Anurita; Chatterjee, Swarnendu (Respiratory medicine, 2024)
Asthma treatments based solely on diagnostic label do not benefit patients equally. To identify patient traits that may be associated with improved treatment response to regular inhaled corticosteroid (ICSs) dosing with short-acting β -agonist reliever or ICS/formoterol-containing therapy, a systematic literature review (SLR) was conducted. Searches of databases including MEDLINE and Embase identified randomised controlled trials (RCTs) of patients with asthma, aged ≥12 years, published 1998-2022, containing ≥1 regular ICS dosing or ICS/formoterol-containing treatment arm, and reporting patient traits and outcomes of interest. Relevant data was extracted and underwent a feasibility assessment to determine suitability for meta-analysis. The SLR identified 39 RCTs of 72,740 patients and 90 treatment arms, reporting 11 traits and 11 outcomes. Five patient traits (age, body mass index, FEV , smoking history, asthma control) and five outcomes (exacerbation rate, lung function, asthma control, adherence, time to first exacerbation) were deemed feasible for inclusion in meta-analyses due to sufficient comparable reporting. Subgroups of clinical outcomes stratified by levels of patient traits were reported in 16 RCTs. A systematic review of studies of regular ICS dosing with SABA or ICS/formoterol-containing treatment strategies in asthma identified consistent reporting of five traits and outcomes, allowing exploration of associations with treatment response. Conversely, many other traits and outcomes, although being potentially relevant, were inconsistently reported and limited subgroup reporting meant analyses of treatment response for subgroups of traits was not possible. We recommend more consistent measurement and reporting of clinically relevant patient traits and outcomes in respiratory RCTs.